A Study of Echocardiographic Changes Among the Patients of COPD - Uddin, SM Afzal; Rahman, MK; Khan, MMR; Rahman, M Moksedur; Islam, MN; Ghose, Sandipan; Huda, MN; Begum, Shahana; Basak, PM; Rahman, M Tuhitur (TAJ: Journal of Teachers Association, 2018)
Background: Chronic Obstructive Pulmonary Disease (COPD) is one of the major health problems and causes of chronic morbidity and mortality in Bangladesh as well as worldwide. Echocardiogram was performed to observe changes among the patients of COPD. Objectives: To observe echocardiographic changes among the patients of COPD. Methods: It was a cross-sectional observational study carried out in the Department of Medicine, Rajshahi Medical College Hospital, Rajshahi from July, 2010 to June, 2012. According to inclusion and exclusion criteria 64 people aged 40-70 years having COPD were selected. Thorough history, physical examination and spirometric along with echocardiographic assessment were done. Results: In case of COPD, 22(34.4%) cases showed echocardiographic changes and 42(65.6%) cases showed normal echocardiogram. Conclusion: In this study, Echocardiographic changes were 34.4% in COPD patients which would help in early detection of cardiac morbidity among those patients and to manage them accordingly. TAJ 2015; 28(1): 16-20